Reading the Sowetan's mediation of the public's response to the Jacob Zuma rape trial: a critical discourse analysis - Stent, Alison (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2007)
In this minithesis I conduct a critical discourse analysis to take on a double-pronged task. On the one hand I explore the social phenomenon of the contestation between supporters of then-ANC deputy president Jacob Zuma and supporters of his rape accuser. The trial, which took place in the Johannesburg High Court between mid-February and early May 2006, stirred intense public interest, both locally and internationally. The performance of thousands of Zuma's supporters and a far smaller number of gender rights lobby groups, both of whom kept a presence outside the court building throughout the trial, received similar attention. Second, I examine how the Sowetan, a national daily tabloid with a black, middle-class readership, mediated the trial through pictures of the theatre outside the court and letters to the editor. The study is informed by post-Marxist and cultural studies perspectives, both approaches that are concerned with issues of power, ideology and the circulation of meaning within specific sociocultural contexts. A rudimentary thematic content analysis draws out some of the main themes from the material, while the critical discourse analysis is located within a theoretical framework based on concepts from Laclau & Mouffe's theory of meaning, which assumes a power struggle between contesting positions seeking to invalidate one another and to either challenge or support existing hegemonies. This is further informed by, first, Laclau's theorisation of populism, which assumes that diverse groupings can unite under a demagogue's banner in shared antagonism towards existing power, and second, by concepts from Mamdani's theorisation of power and resistance in colonial and post-colonial Africa, which explicates three overarching ideological discourses of human rights, social justice and traditional ethnic practices. The study, then, explores how these three discourses were operationalised by the localised contestations over the trial.
Keywords: Zuma, Jacob -- Trials, litigation, etc.; Zuma, Jacob -- Public opinion; Sowetan (Johannesburg, -- South Africa); Populism -- South Africa; Social choice -- South Africa; Social justice -- South Africa; Ethnicity -- Political aspects -- South Africa; Rape -- Public opinion; Women -- Crimes against -- South Africa; Sex discrimination against women -- South Africa; Trials (Rape) -- South Africa; Rape in mass media; Crime and the press -- South Africa; Mass media and women -- South Africa